THEORIES & PRACTICE. - Kohler, E. L. (The Accounting Review, 1940)
A number of papers in the March 1940 issue of the journal The Accounting Review, dealing with Federal accounting and auditing, have been prepared by persons familiar with practices now being followed and are both descriptive and critical in character. These papers will furnish a background for accountants who desire to know something about Federal accounting procedures, and it is hoped that they may in some degree crystallize the broad criticisms which have frequently been leveled at theories of Federal fiscal responsibility: many of which have been inherited from the days of intellectual Alexander Hamilton. The Budget and Accounting Act of 1921 placed the responsibility for the accounting systems of the government in the hands of a Comptroller General who as head of the United States General Accounting Office was made independent of current administrations. But the U.S. Congress neglected to provide adequate machinery to control the activities of the Comptroller. Under existing law, it may be worth noting that the person accountable for expenditures of Federal departments is not even the administrator but the lowly "disbursing officer," an employee of the administrator charged with the duty of paying obligations incurred by others.